Lorazepam Challenge for Individuals at Varying Genetic Risk for Alzheimer Disease. (October 2017) - Stonnington, Cynthia M.; Harel, Brian; Locke, Dona E.C.; Hentz, Joseph G.; Zhang, Nan; Maruff, Paul; Caselli, Richard J.
Abstract : Introduction: This study set out to clarify the differential acute cognitive impact of lorazepam based on varying genetic risk for Alzheimer disease. Methods: Fifty-seven cognitively unimpaired individuals aged 51 to 88, genotyped according to apolipoprotein E (APOE) and translocase of outer mitochondrial membrane (40 homolog) poly-T lengths, completed cognitive testing before, 2.5 and 5 hours after receiving a 1 mg dose of lorazepam. Results: Post-lorazepam, there were significant ( P <0.05) declines from baseline in memory, psychomotor processing speed, and executive function. At 2.5 hours, the magnitude of this lorazepam-induced cognitive change was significantly greater in the APOE3/4 group than in the APOE3/3 group for tests of working memory and visuospatial memory/executive function. At 5 hours postchallenge, verbal memory and working memory deficits persisted in the APOE3/4 group compared with the APOE3/3 group. At 5 hours after lorazepam challenge, as compared with the very long/very long group, the short/short group performed slightly worse on a test of working memory ( P <0.05), but no other differences were observed among translocase of the outer mitochondrial membrane 40 homolog poly-T variant groups. Discussion: The lorazepam challenge may be unmasking presymptomatic cognitive dysfunction associated with APOE4 carriage.